2018
DOI: 10.3390/atmos9010028
|View full text |Cite|
|
Sign up to set email alerts
|

New Setup of the UAS ALADINA for Measuring Boundary Layer Properties, Atmospheric Particles and Solar Radiation

Abstract: Abstract:The unmanned research aircraft ALADINA (Application of Light-weight Aircraft for Detecting in situ Aerosols) has been established as an important tool for boundary layer research. For simplified integration of additional sensor payload, a flexible and reliable data acquisition system was developed at the Institute of Flight Guidance, Technische Universität (TU) Braunschweig. The instrumentation consists of sensors for temperature, humidity, three-dimensional wind vector, position, black carbon, irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 50 publications
(94 reference statements)
6
56
0
Order By: Relevance
“…This is supported by the analysis of Adler et al (2018), who perform in a consistent manner an analysis for 11 IOPs 15 and we find a good agreement between these two studies. Additionally, Adler et al (2018) investigated LLC characteristics (vertical extent, coverage, onset time and horizontal distribution and evolution), as well as the intra-night variability of boundary layer conditions and processes relevant for LLC formation. present a detailed statistical analysis on the characteristics of the LLC and the dynamics in the lower atmosphere for a 41 day period.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is supported by the analysis of Adler et al (2018), who perform in a consistent manner an analysis for 11 IOPs 15 and we find a good agreement between these two studies. Additionally, Adler et al (2018) investigated LLC characteristics (vertical extent, coverage, onset time and horizontal distribution and evolution), as well as the intra-night variability of boundary layer conditions and processes relevant for LLC formation. present a detailed statistical analysis on the characteristics of the LLC and the dynamics in the lower atmosphere for a 41 day period.…”
Section: Introductionsupporting
confidence: 89%
“…The layer of the maximum change 10 corresponds to the level of the NLLJ maximum. This is in agreement with results in Adler et al (2018), who found that on average cooling is the main process leading to the increase of RH and saturation, while moistening contributes only little.…”
supporting
confidence: 93%
See 3 more Smart Citations